Smart Security in Smart City Using Naïve Bayes and RSA - Junaidi Junaidi; R Roslina; B. Herawan Hayadi (Proceeding of International Conference on Information Science and Technology Innovation (ICoSTEC), 2023)
As all major cities adopt the concept of smart cities, concerns arise among the public regarding data security and privacy. The constant threat of attacks on confidentiality, integrity and accessibility of data makes it vulnerable to cyber attacks. The increasing use of IoT devices also increases the potential for cyber attacks that can harm all IoT users. Therefore, it is crucial for city governments to be aware of data security issues related to smart spaces, services, and citizen security, and to provide solutions to existing problems by making maximum policies related to the implementation of smart city concepts. From the above explanation, the author is taking the analysis step with the title "Analysis of Naive Bayes Classifier and Rsa (Rivest Shamir Adleman) Combination in Smart Security in the Implementation of Smart City in Pemko Medan" where the benefits that can be obtained are to gain deeper understanding of Smart Security level, obtain information about the Smart Securty level, and classify the stage of Smart Securty using the combination of Naive Bayes Classifier and Rsa (Rivest Shamir Adleman) in the implementation of Smart City in Pemko Medan.